THE INFLUENCE OF PEER TUTORING-BASED HUMANISTIC MATHEMATICS LEARNING ON THE MOTIVATION OF LEARNING MATHEMATICS OF HIGH SCHOOL STUDENTS - Noperta, Noperta; Sari, Maila (Universitas Tanjungpura, 2023)
Many students are not comfortable studying mathematics and think mathematics is a boring subject. So students do not have good motivation in learning mathematics. This is due to the inhumane teaching of mathematics. This research was conducted to assess students' motivation when learning humanistic mathematics based on peer tutors. This research is experimental research with a one group pretest-posttest design. Data were collected using the Attention, Relevance, Confidence, Satisfaction (ARCS) motivation questionnaire. The data were analyzed using the Wilcoxon test because the data obtained were not normally distributed. The results obtained that the value of sig. (2-tailed) of 0.000 is smaller than 0.05 (0.000 0.05), which means that the hypothesis is accepted. So that there is a significant comparison between students' mathematics learning motivation before and after applying humanistic mathematics learning based on peer tutors or there is a significant influence between peer tutor-based humanistic mathematics learning on students' mathematics learning motivation.